An evolutionary theory of suicide - Balázs Szentes; Caroline D. Thomas (Games, 2013)
We analyze a model in which individuals have hereditary reproductive types. The reproductive value of an individual is determined by her reproductive type and the amount of resources she can access. We introduce the possibility of suicide and assume it is also a genetic trait that interacts with the reproductive type of an individual. The main result of the paper is that populations where suicide is possible grow faster than other populations.
Keywords: 330; suicide; evolution; group selection